2020
DOI: 10.1371/journal.pone.0237040
|View full text |Cite
|
Sign up to set email alerts
|

Effects of histamine on human periodontal ligament fibroblasts under simulated orthodontic pressure

Abstract: As type-I-allergies show an increasing prevalence in the general populace, orthodontic patients may also be affected by histamine release during treatment. Human periodontal ligament fibroblasts (PDLF) are regulators of orthodontic tooth movement. However, the impact of histamine on PDLF in this regard is unknown. Therefore PDLF were incubated without or with an orthodontic compressive force of 2g/cm 2 with and without additional histamine. To assess the role of histamine-1-receptor (H1R) H1R-antagonist cetiri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…In our study, increased PTGS2 expression was accompanied by elevated RANKL expression due to pressure. OPG secretion was downregulated, which could also been shown in experiments with a similar experimental setup in the past [45][46][47][48]. A significantly increased RANKL expression was detected after compression with leptin treatment.…”
Section: Discussionsupporting
confidence: 74%
“…In our study, increased PTGS2 expression was accompanied by elevated RANKL expression due to pressure. OPG secretion was downregulated, which could also been shown in experiments with a similar experimental setup in the past [45][46][47][48]. A significantly increased RANKL expression was detected after compression with leptin treatment.…”
Section: Discussionsupporting
confidence: 74%
“…Antihistamine agents can competitively inhibit histamine H 1 ‐receptors so that to antagonize the histamine effects, which have been widely used for the treatment of allergic and ulcer symptoms [7,8]. In this study, six antihistamine drugs (such as orphenadrine, meclizine, terfenadine, mequitazine, dioxopromethazine, and carbinoxamine) containing a chiral carbon atom were selected as the target analytes (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[19] investigated the chiral separation of five antihistamine drugs on Chiralpak IA and Chiralpak ID columns to obtain the complete resolution of meclizine, mequitazine, and carbinoxamine enantiomers. Besides, the enantiomeric separation of meclizine, orphenadrine, terfenadine, and carbinoxamine on three polysaccharide‐based CSPs (Lux Cellulose‐1, Lux Cellulose‐2, and Lux Amylose‐2) has been reported [7,20]. Among these commercially available CSPs materials used for chiral separation in HPLC, polysaccharide‐based CSPs are the most commonly used materials contributed to the high enantioselectivity and excellent loading capacity over a broad range of enantiomers [21–23].…”
Section: Introductionmentioning
confidence: 99%
“…An in vitro study showed that histamine induced the release of prostaglandin E 2 via H1 receptor-mediated Ca 2+ signaling in PDL cells [14]. More recently published research demonstrated that human PDL fibroblasts express H1-, H2-, and H4-receptors [15]. In previous studies a wide variety of drugs, which can be diffusely consumed even without the medical prescription at the same time of an orthodontic treatment, have already been investigated regarding a potential influence on OTM [16]; however, to date little is known about the effects of cetirizine on OTM.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the prevalence of allergies mediated by the H1-receptor, the use of cetirizine generally increased in the population. Due to its systemic anti-inflammatory action, an impact on OTM is to be considered, as OTM is also a (sterile) inflammatory process at the molecular level mediated by periodontal ligament fibroblasts [31], which have been shown before to change their expression pattern under the influence of histamine [15]. This animal study, therefore, aims to further investigate the influence of the H1-receptor antagonist cetirizine on the rate of OTM, cranial growth, root resorption, and periodontal bone loss in an in vivo rat model of orthodontic tooth movement.…”
Section: Introductionmentioning
confidence: 99%